Diabetes and pregnancy : a guide to a healthy pregnancy for women with type 1, type 2, or gestational diabetes - Sacks, David A. (Alexandria, Va. : American Diabetes Association, 2011)
'Diabetes and Pregnancyis a comprehensive guide for women with Type 1, Type 2, or gestational diabetes. Combining and updating the content from bothDiabetes and Pregnancy: What to ExpectandGestational Diabetes: What to Expect, this newly revised volume contains all the information needed for a woman to plan, conceive, and deliver a healthy baby. Meal planning, exercise, insulin therapy, and monitoring are covered. Other subjects related to pregnancy are also discussed, such as the different stages of an unborn babys' development, what tests to expect during pregnancy, labor and delivery, and birth control'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Diabetes in pregnancy